Wrestling with the Right Side Of History: On Discourse, Pedagogy, Time, and the Ethics of Critical Scholarship - Gounari, Panayota (The Greek Review of Social Research, 2025)
This reflexive piece offers a critical reflection on my scholarly trajectory by mapping the theoretical and political commitments that have shaped my academic work over time. Drawing from lived experiences of dislocation, and political urgency, I trace how my scholarship has developed across three interrelated thematic domains: (1) the discursive construction and normalization of far-right authoritarianism, (2) the ideological functions of education as a contested site within capitalist structures, and (3) the centrality of historical thinking as a methodological, epistemological, and political imperative. Grounded in Critical Theory —particularly the Frankfurt School— and articulated through Critical Discourse Studies and Critical Pedagogy, I examine how my work has aimed to expose and disrupt the logics of neoliberalism, authoritarianism, and epistemic violence. Across these domains, I argue that critique is not a methodological add-on but a historically and politically situated praxis. This paper is both an intellectual memoir and a synthesis of scholarly contributions, foregrounding the imperative to historicize, politicize, and radicalize intellectual labor in the service of social transformation.